Biological Characteristics and Whole Genome Analysis of vB_VpP_3, a Bacteriophage against Multi-drug Resistant Vibrio parahaemolyticus - LIU Qingqing, ZHANG Ming, YANG Wenjing, LIU Ke, LI Fan, LI Xuepeng, LI Jianrong, ZHANG Defu (Shipin Kexue)
Objective: To isolate bacteriophages with strong lytic activity against multi-drug resistant Vibrio parahaemolyticus. Methods: Using V. parahaemolyticus as host bacteria, bacteriophages were isolated and purified from seafood, and their biological characteristics and whole genome were analyzed. Results: Phage vB_VpP_3, which was isolated from crab, had a narrow host range and high host specificity with an optimal multiplicity of infection 0.1 and a maximum adsorption rate of 93%. The one-step growth curve showed that the latent period of the phage was 15 min, the average burst size was 110 PFU, and it was highly tolerant to the environment. Phage vB_VpP_3 belonged to the order Caudovirales of the family Podoviridae with a regular icosahedral head about 60 nm in diameter and a non-contractile tail about 20 nm in length. Its genome was double-stranded linear DNA with a total length of 42 459 bp and a total GC content of 46.87% without any virulence or drug resistance genes. Conclusion: Bacteriophage vB_VpP_3 was highly safe and could be used for biological control of multi-drug resistant V. parahaemolyticus.